2000
DOI: 10.1038/sj.bjp.0703729
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced contractile response to thrombin in the pregnant rat myometrium

Abstract: 1 Thrombin causes various cellular events by activating protease-activated receptors (PARs). Here, we showed, for the ®rst time, that thrombin induced myometrial contraction. To determine the mechanism of thrombin-induced myometrial contraction, we simultaneously measured intracellular Ca 2+ concentration ([Ca 2+ ] i ) and tension of fura-PE3-loaded rat myometrium using front-surfacē uorimetry. The expression of thrombin receptor mRNA in the rat myometrium were determined by reverse transcription-polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…The thermal cycle profile used for the amplification of PAR1, PAR2, PAR3 and PAR4 fragments was composed of the initial denaturation at 94°C, for 2 min and the following 40‐cycle amplification step consisting of 15 s denaturation at 94°C, 15 s annealing at 52°C and 30 s extension at 68°C. The expression of β ‐actin was determined as a control as described previously ( Shintani et al ., 2000a ). The RT–PCR products were separated on 3% agarose gel containing 0.05 μ g ml −1 ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The thermal cycle profile used for the amplification of PAR1, PAR2, PAR3 and PAR4 fragments was composed of the initial denaturation at 94°C, for 2 min and the following 40‐cycle amplification step consisting of 15 s denaturation at 94°C, 15 s annealing at 52°C and 30 s extension at 68°C. The expression of β ‐actin was determined as a control as described previously ( Shintani et al ., 2000a ). The RT–PCR products were separated on 3% agarose gel containing 0.05 μ g ml −1 ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that thrombin and trypsin induced an enhanced myometrial contraction in the pregnant rat myometrium ( Shintani et al ., 2000a ; 2001 ). Among the known four members of PARs, PAR1 was the only receptor expressed in the rat myometrium, and it was found to be upregulated in the pregnant rat myometrium ( Shintani et al ., 2000a ; 2001 ). The upregulation of PAR1 was thus considered to contribute to the enhancement of the contractile response to thrombin in the pregnant rat ( Shintani et al ., 2000a ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The uterotonic effect of thrombin may be exerted by its receptor, PAR-1, which mediates many of the effects of thrombin on platelet activation[153,154], proinflammatory cytokine secretion[17,155,156], local tissue remodeling after injury[157,158], fetal blood vessel development and stabilization[159161], as well as uterine contractions[162164]. Indeed, in a study on stem cells gene expression, PAR-2 and PAR-1 were among the top 25 up-regulated genes in stem cells of amniotic fluid origin[165], suggesting that thrombin can exert its intracellular and proinflammatory effect via local mechanisms through its receptor.…”
Section: Commentsmentioning
confidence: 99%